If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6t-6=18
We move all terms to the left:
-6t-6-(18)=0
We add all the numbers together, and all the variables
-6t-24=0
We move all terms containing t to the left, all other terms to the right
-6t=24
t=24/-6
t=-4
| y=-1/4*1+3 | | 4a+3=-9+2a | | 2x-2A=3B | | -9=10x+81 | | 2n+10+4n=15+6n | | 1/5+n=2/5 | | -1/2(4x-6)=-4x+15 | | Y-3=-2(x+2) | | 10x-6x+12=8x+40 | | 8+3d=3d-2 | | v+1+6=-3+6v | | f+2.3=9.4 | | i-15=9 | | 10(-3/5x+4)=-21(2/7x-1) | | 10=-r | | -240=15x | | 9.2-8.9=n | | -m+9=13 | | 34=r+15 | | y=-1/4*0+3 | | 3.3x=5 | | 6x+19+85=180 | | 4.7+2.1=v | | 10b−5=15 | | 3+k4=14 | | 3p-7p=-7(p-5) | | (x+7)(x+3)=10(x+2)+2 | | -121=-11p | | 2x-6=−2(x−3) | | 8.4y-6.8=16.4 | | n+7=-n-5 | | 3w=1.5 |